Consumer Behavior Regarding Usage Of Food Ordering Applications In And Around Chandigarh - Sharma, Neeraj; Saraf, Kanav (Gyan Management Journal, 2020)
Significance of utilizing the Internet in marketing mixes is being recognized by numerous marketers. But only few researchers has experimentally tested the critical variables that impact an individual’s decision while purchasing items or services on the web. Based on the aperture in the literature, the motive of the study is to comprehend the impression of Electronic Online Food Ordering. The main consideration that represses the person who has never ordered anything through web is a mental barrier regarding usage of Internet for Food Ordering and discomfort in using the apps on mobile for food ordering. Another reason for not ordering food through internet is fear of hacking of financial data or its misuse. Consumers’ Perceptions of Online Ordering varies from person to person. The intention of this research work is to help food service providers to better design their electronic ordering channels. The most significant attribute while ordering on web is order exactness. After that it is convenience and simplicity of placing an order. Telephone calls are most widely recognized medium for placing an order, in spite of availability of the internet and phone apps. Electronically placing an order is developing; however the respondents said they place little more than 38 percent of their orders on the restaurant’s website or app. A main ramification is that restaurateurs should give guarantee that their ordering systems give impression of control and convenience to the user. Another factor that needs to be focused is that clients prefer restaurants with home delivery service for online ordering. It is found in this research that there is a growing tendency among youth to order food only more frequently through online apps available on Mobile phones.